"أثر الفساد عمى النمو الإقتصادي في الدول العربية خلال الفترة -2017/2003-" - مسعود, معتوقي; عبد الرحمان, ريمي; وليد, حريز بلقاسم (University of eloued جامعة الوادي, 2019)
"تهدف هذه الدراسة إلى تحليل أثر الفساد على النمو الاقتصادي في الدول العربية خلال الفترة 2003-2017 مستعملين أدوات القياس الاقتصادي و المتمثلة في نماذج بيانات البانل من خلال نتائج الدراسة القياسية الإشارة الموجبة لمعامل مؤشر مدركات الفساد CPI (0.650) يدل على الأثر الإيجابي للفساد على النمو في الدول العربية وهذا ما يخالف النظرية الاقتصادية ولكن هذا الأثر غير معنوي لأن قيمة المعنوية تساوي (0.336) وهي أكبر من 0.05 . ""The objective of this study is to analyze the impact of corruption on economic growth in the Arab countries during the period 2003-2017 using economic measuring tools, We found that the parameter of the. The positive sign of the CPI coefficient (0.650) indicates the positive effect of corruption on growth in the Arab countries. This is contrary to the economic theory, but this effect is not significant because the value of the significance is 0.336, which is greater than 0.05. "
مذكرة ماستر اقتصاد كمي
Keywords: الفساد، النمو الاقتصادي، نماذج بانل; Corruption, Economic Growth, Banel Models.